The Relationship Between Mothers’ Frequency of Visits to the Posyandu and the Nutritional Status of Toddlers in Jemah Village, West Java, Indonesia - Reviani, Nia; Handayani Tampubolon, Christine (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Nutrition is a key determinant of human health and development, especially in the toddler period, when inadequate intake can quickly lead to growth and health problems. Objective: To determine the relationship between the frequency of maternal visits to integrated health posts (Posyandu) and the nutritional status of toddlers in Jemah Village, Jati Gede District, Sumedang Regency. Method: This descriptive analytic study used a cross-sectional design. Data were collected through observation with an accidental sampling technique from 50 mothers and toddlers registered at Posyandu Mawar I–IV in Jemah Village. Result and Discussion: Most mothers were 26–35 years old, had a high school education, and were housewives. Most toddlers had good nutritional status, and 82% of respondents routinely visited the integrated health posts. Statistical analysis showed a significant positive relationship between visit frequency and toddler nutritional status (p = 0.001), indicating a very strong correlation. Conclusions: Routine maternal visits to integrated health posts are strongly associated with better nutritional status among toddlers in Jemah Village.